OJK and Bank Indonesia Regulatory Compliance as a Determining Factor of Fintech Business Feasibility in Indonesia - Reynelda Sheba; Maria Ulfah (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Indonesia's fintech industry has developed rapidly over the past decade, ranking among the most dynamic in the national digital economy ecosystem. Amid this rapid growth, compliance with regulations issued by the Financial Services Authority (OJK) and Bank Indonesia (BI) has become a decisive factor in determining fintech business feasibility to operate legally and sustainably. This study aims to analyze the role of OJK and BI regulatory compliance as a determining factor of fintech business feasibility in Indonesia. The method used is a literature review with a qualitative descriptive approach, examining relevant regulations, scientific publications, and recent industry reports. The findings show that regulatory compliance is not merely a legal obligation but a strategic foundation that determines investor confidence, consumer protection, and the operational continuity of fintech businesses. Compliance with prevailing rules creates a healthy business climate and significantly reduces potential legal and reputational risks. Conversely, non-compliance has been clearly proven to be a main factor behind the failure of several fintech businesses in Indonesia, due to license revocation or loss of public trust. Therefore, integrating regulatory compliance aspects into business feasibility studies is crucial. This research is expected to contribute to enriching the understanding of legal aspects in business feasibility studies, particularly in the rapidly growing digital financial services sector.